The impact of domestic tourism on perspectives of Australia's national capital - Mules, T.; Pforr, Christof; Ritchie, B. (The Haworth Press, 2007)
Political national capitals provide the location for national institutions, represent national values and are the seat of government. Despite the importance of political national capital cities as tourism destinations, they may be faced with a poor image and perceptions from potential tourists because of their association with government and negative media coverage. This paper presents research undertaken to examine the images, values and perceptions that Australian’s hold of Canberra (the national capital) and to explore whether perceptions differed based on previous visitation. The results suggest that a significant number of images and perceptions changed if respondents had visited Canberra previously. Furthermore, a visit can lead to an increased agreement that the national capital represents national values. Three cluster segments were also determined and named the misinformed, the capital lovers and the uninformed based on their characteristics. The paper concludes by suggesting both tourism agencies and national capital agencies should work more closely together in fostering greater visitation to political capitals which will help to build feelings of nationhood as well as correct negative destination perceptions.